A comparison of consumer characteristics and their influence on the use of electronic word-of-mouth - Beheshti, Sina (Eastern Mediterranean University EMU, 2017)
This thesis examines the impact of word-of-mouth concept in social media on consumers’ decision-making for purchasing a product. One hundred and fifty-four responses from Eastern Mediterranean University, Turkish Cypriot and Turkish customers were used in the questionnaire. T-test and ANOVA analysis were conducted to examine the relationship between word-of-mouth and its determinants. The results of independent T-test show that both male and female have a significant difference in their consideration of offline word-of-mouth messages for commercial activities. Results also show that Females rely more on word-of-mouth than males for commercial purposes. The results of ANOVA test explain that younger respondents were more eager to use online networks for commercial purposes than their older counterparts. There was no significant difference between people’s job status in their use of social media for commercial purposes, online and offline word-of-mouth reliance. Keywords: Word-of-Mouth, Social Media, Customer Satisfaction, T-test, ANOVA test, North Cyprus.

ÖZ: Bu tez, tüketicilerin bir ürün satın alımında karar verme konusundaki sosyal medyadaki ağız dan ağıza (dilden dile) kavramının etkisini inceler. 154 katılımcının kullanıldığı ankette, Doğuakdeniz üniversitesi öğrencileri, yerel kıbrıs Türk halkı ve Türk vatandaşı müşterileri yeralmaktadır. Çalışmada ağızdan ağıza kavramı ile kendisinin belirleyicileri arasındaki ilişkiyi bağımsız t-testi, tek yönlü anova analizi ve faktör analizi kullanılarak tespit edilmiştir. Faktör analizinin sonuçları, üç ana bileşenin olduğunu ortaya koymaktadır; İlk insanlar çevrimiçi platformun araçlarına güveniyorlar, İkincisi, çevrimiçi araçlardan haberdar olduklarını ve sonuncusu ticari faaliyetler için sosyal ağ kullanıyor olmaları. Bağımsız T testi sonuçları, hem erkek hem de kadınların çevrimdışı WOM mesajlarının ticari faaliyetler için dikkate alınmasında anlamlı bir farklılığa sahip olduğunu göstermektedir. Elde edilen sonuçlar ayrıca, Kadınların ticari amaçlar için erkeklerden daha fazla WOM'a güveniyor olduğunu göstermektedir. ANOVA testinin sonuçları, genç katılımcıların çevrimiçi ağları ticari amaçlı olarak eski meslektaşlarından daha istekli olduklarını açıklıyor. Ticari amaçla, çevrimiçi ve çevrimdışı WOM güvenirliği için sosyal medya kullanımında, insanların iş durumları arasında anlamlı bir fark bulunmamaktadır. Anahtar Kelimeler: Ağızdan ağıza, Sosyal Medya, Müşteri memnuniyeti, Faktör Analizi, Bağımsız T-testi, Tek yönlü Anava analizi, Kuzey Kıbrıs.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing-Social Media-Word-of-mouth-Consumers' Decision Making; Word-of-mouth advertising-Consumer satisfaction-Marketing; Word-of-mouth advertising-Consumer satisfaction-Marketing